Crisis as opportunity? Emergent groups, crisis relief, and social innovation in response to Covid-19 - Soderbergh, Jenny (Graduate School of Business (GSB), 2023)
The Covid-19 pandemic brought the world to a halt in early 2020. In South Africa, as in many places around the world, the government instituted a strict national lockdown beginning at the end of March 2020 which catalyzed interconnected social and economic crises. However, the lockdown also catalyzed a proliferation of emergent crisis response groups and initiatives aimed at alleviating suffering. This qualitative case study follows the emergence and progression of eight such emergent response groups located in the Western Cape to explore the relationship between crisis response and social innovation. Over the course of one year, crisis responses are detailed across three temporal brackets: Emergence (initial crisis response), Plateau (sustained crisis response), and Evolution (differing response paths). These temporal brackets contain key themes within them, as well as enablers and barriers for transitioning between short-term crisis response and longer-term systemic change ambitions. The findings show that emergent response groups do persist in efforts well past the initial onset of a crisis and that they make intentional decisions around how to transition from crisis response towards longer-term change ambitions. Taking an institutional work lens to social innovation, this study shows that emergent response groups engage with and challenge multiple performative institutional dimensions in their work and that they have the ability, and often the desire, to affect more systemic change over time. This work aims to bring the academic conversations of crisis response and social innovation closer together, with a focus on individual and informal group agency, while also providing practical implications for supporting emergent response groups and social innovation in the face of future disruptions and crises.